EFFECT OF THE SUPPLEMENTATION OF ORGANIC ACIDS ON PRODUCTIVE PARAMETERS IN BROILERS - Gonzáles A., Sergio (2013)
The objective of the study was to evaluate the effect of a mixture of organic acids and their salts on the productive parameters in broilers. A total of 133 1-day-old male chicks of the Cobb Vantress 500 Line were distributed in three treatments with three repetitions per treatment: T1, diet with Zinc-Bacitracin; T2, diet containing organic acids; and T3, control treatment, diet without growth promoter. At 42 days of age, feed conversion in T2 was 5.2% less than in T3 (p<0.05); however, no statistical differences were observed between treatments regarding body weight, body weight gain, feed consumption, mortality rate and productive efficiency index. The results showed that organic acids can efficiently replace the use of antibiotics as growth promoters in the diets of broilers